When the larger objective matters more: support workers' epistemic and deontic authority over adult service‐users. Issue 8 (18th June 2019) - Antaki, Charles; Webb, Joseph
Abstract: We report on how support workers sometimes over‐ride the wishes of people living with cognitive impairments. This can happen when they are both involved in some project (such as an institutionally‐managed game, a physical journey, an educational activity and so on). The support worker might use their deontic authority (to propose, decide or announce future actions) to do things that advance the over‐arching project, in spite of proposals for what are cast as diversions from the person with impairments. They might also use their epistemic authority (their greater knowledge or cognitive capacity) to trump their clients' choices and preferences in subordinate projects. Not orienting to suggested courses of actions is generally interactionally dispreferred and troublesome, but, although the providers do sometimes orient to their actions as balking their clients' wishes, they usually do not, and encounter little resistance. We discuss how people with disabilities may resist or palliate such loss of control, and the dilemmas that support staff face in carrying out their duties.